PENGARUH MODEL PEMBELAJARAN TAI DIPADUKAN DENGAN LT TERHADAP INTERAKSI SOSIAL DAN HASIL BELAJAR SISWA - Izzatunnisa, Izzatunnisa; Nufida, Baiq Asma; Hulyadi, Hulyadi (IKIP Mataram, 2016)
This research target was toidentify the influence of Team Assisted Individualization (TAI) type of Cooperative Learning Model accompanied with LearningTogether (LT) to student social interaction andstudy result. This was quasi experimental with post-test only control group design. Research subject was 63 student of 10th grade who was divided onto 35 student of experiment group and 28 student of control group. Experiment group was learned by Team Assisted Individualization (TAI) accompanied with LearningTogether (LT) and control group by conventional expository model. There were instrument on this research: (1) treatment instrument consist of Syllabus, RPP (teaching plant), and LKS (work sheet); (2) evaluation instrument consist of RPP observation sheet, social interaction questionnaire, social interaction observation sheet, and achievement test. Data was collected by observation, questionnaire, and test technique. Data was analyzed by descriptive analysis and independent sample t-test through SPSS 16.0 for windows as hypothetic test. Based on questionnaire, student social interaction analysis result showed enhancement between before and after treatment, from 71.67 % to 75.76 %, and based on direct observation, 67.50 %, on good category. Student study result enhancement analysis result was showed by their classical complete study, form 8.57 % to 94.28%, and t-test of study result was divine significance value 0.000 (<0.05), so that Ho was denied and Ha was accepted. So, it was concluded that: (1) Team Assisted Individualization (TAI) type of Cooperative Learning Model accompanied with LearningTogether (LT) was influence to student social interaction; (2) Team Assisted Individualization (TAI) type of Cooperative Learning Model accompanied with LearningTogether (LT) was influence to student study result.